Analisis Kesesuaian Parameter Lingkungan Untuk Kegiatan Ranching Kuda Laut ( Hyppocampus sp ) di Perairan Pulau Barrang Caddi - syafriman ali (Hasanuddin University, 2018)
Cultivation of marine biota (maricultur) in the waters of Makassar city has increased, both in terms of land area and type of cultivation. Cultivation business is an alternative business that can improve people's welfare. Cultivation activities need to pay attention to the sustainability and availability of seeds in nature. Activities that can increase the amount of seed production in nature so that an organism is not extinct is Sea Ranching. Sea ranching is more active in environmental conservation because in addition to habitat restoration done fish restocking in the framework of stock enhancement activities. Development of Sea Ranching activities, need to pay attention to environmental parameters. This is because the parameters including factors greatly affect the extent of the area and location of the development of cultivation activities and Sea Ranching (Anggoro, 2004). The results of the research conducted on the island of Barrang Caddi city of Makassar, assess the level of conformity of environmental parameters for sea horse ranching activities (Hyppocampus sp) shows that the area of Pulau (4 Ha) waters, the appropriate category (1,081 Ha), the corresponding category (2,372 Ha) and Non-Conforming Category (0.610 Ha).